Poling of ß-poly(vinylidene fluoride): dielectric and IR spectroscopy studies - Sencadas, Vítor João Gomes Silva (2005)
ß-Poly(vinylidene fluoride) (ß-PVDF) exhibits ferroelectric properties due to the special arrangement of the chain units in the crystalline phase. The piezoelectric properties of the material can be optimised by poling the original stretched film. The main effect of the poling process is the alignment of the randomly organised dipolar moments against the applied field. In this work, poled and non-poled ß-PVDF from the same batch are characterised by dielectric spectroscopy. The origin of the electrical and mechanical response of poled and non-poled ß-PVDF were further explored by far IR spectroscopy and discussed on a molecular level. The main effect of the poling process on-the dielectric response of the-material is a small increase of the dielectric constant due to the 'preferential alignment of the main dipolar contribution and a slight decrease of the dielectric loss, due to the more organized amorphous structure. The conductivity is strongly increased by poling, especially the high-temperature conductivity, ascribed mainly to hopping conductivity due to free charges induced during poling. FTIR experiments indicate that the origin of these effects and also of the variations in the thermo-mechanical response of the material can be found in the reorientation of the crystalline dipoles along the poling field, together with a partial reduction of the amount of alpha phase and an increase of the amount of ß phase. The alpha to beta transformation, mainly due to the stretching process, seems to be optimized by the poling process.